SUPERVISI KLINIS DALAM PEMBELAJARAN - Roaina Roaina (UNIVERSITAS BENGKULU, 2019)
This study described the clinical supervision in learning civic education at Senior High School 1 Muara Pinang Empat Lawang Regency. The methode used in this study was descriptive and qualitative methode. the data were obtained from interview, observation and documentation. The collected data then analyzed with descriptive qualitative. The result of data reveal that clinical supervision in learning civic education at Senior High School 1 Muara Pinang Empat Lawang Regency has been successful and has a significant impact for improvement of learning civic education and for improving the competence of teachers of civic education subjects.